Effects of irisin and exercise on adropin and betatrophin in a new metabolic syndrome model - Aydin, Suna; Kilinc, Faruk; Ugur, Kader; Aydin, Mustafa Ata; Yalcin, Mehmet Hanifi; Kuloglu, Tuncay; Aydin, Suleyman (Taylor & Francis Ltd, 2024)
Metabolic syndrome (MetS) is a prevalent public health problem. Uric acid (UA) is increased by MetS. We investigated whether administration of UA and 10% fructose (F) would accelerate MetS formation and we also determined the effects of irisin and exercise. We used seven groups of rats. Group 1 (control); group 2 (sham); group 3 (10% F); group 4 (1% UA); group 5 (2% UA); group 6 (10% F + 1% UA); and Group 7, (10% F + 2% UA). After induction of MetS (groups 3 -7), Group 3 was divided into three subgroups: 3A, no further treatment; 3B, irisin treatment; 3C, irisin treatment + exercise. Group 4, 1% UA, which was divided into three subgroups: 4A, no further treatment; 4B, irisin treatment; 4C, Irisin treatment + exercise. Group 5, 2% UA, which was divided into three subgroups: 5A, no further treatment; 5B, irisin treatment; 5C, irisin treatment + exercise. Group 6, 10% F + 1% UA, which was divided into three subgroups: 6A, no further treatment; 6B, irisin treatment; 6C, irisin treatment + exercise. Group 7, 10% F + 2% UA, which was divided into three subgroups: 7A, no further treatment; 7B, irisin treatment; 7C, irisin treatment + exercise., Irisin was administered 10 ng/kg irisin intraperitoneally on Monday, Wednesday, Friday, Sunday each week for 1 month. The exercise animals (in addition to irisin treatment) also were run on a treadmill for 45 min on Monday, Wednesday, Friday, Sunday each week for 1 month. The rats were sacrificed and samples of liver, heart, kidney, pancreas, skeletal muscles and blood were obtained. The amounts of adropin (ADR) and betatrophin in the tissue supernatant and blood were measured using an ELISA method. Immunohistochemistry was used to detect ADR and betatrophin expression in situ in tissue samples. The duration of these experiments varied from 3 and 10 weeks. The order of development of MetS was: group 7, 3 weeks; group 6, 4 weeks; group 5, 6 weeks; group 4, 7 weeks; group 3, 10 weeks. Kidney, liver, heart, pancreas and skeletal muscle tissues are sources of adropin and betatrophin. In these tissues and in the circulation, adropin was decreased significantly, while betatrophin was increased significantly due to MetS; irisin + exercise reversed this situation. We found that the best method for creating a MetS model was F + UA2 supplementation. Our method is rapid and simple. Irisin + exercise was best for preventing MetS.
Keywords: Adropin; betatrophin; body mass index; exercise; fructose; human; irisin; metabolic syndrome; rats; uric acid